The Effect of Tangible on Hemodialysis Patient Satisfaction - Hidayat, Dinnisa Haura Zhafira; Mimanda, Yona; Maikel, Mahesa Paranadipa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
This study aims to find out the effect of tangible on hemodialysis patient satisfaction. The location and year of the study is at Rumah Sakit Haji Jakarta in 2022. The writer believes that there is a positive effect of tangible towards hemodialysis patient satisfaction at Rumah Sakit Haji Jakarta. Method: This study is a quantitative study with a cross-sectional design. The population in this study were every hemodialysis patients at Rumah Sakit Haji Jakarta. The sample of this research was obtained by using consecutive sampling technique with a sample of 118 hemodialysis patients in Rumah Sakit Haji Jakarta. Data collection was done using a questionnaire with 1 month as the length of time for data collection. The data analysis performed is simple linear regression analysis using SPSS 26. From the scale of 4, the description analysis shows that tangible scores an average of 3,37, meanwhile the dimension of patient satisfaction with the highest score of interpersonal behaviour with an average of 3,33 and the lowest score is financial aspect with an average of 3,09. The study shows that tangible gives positive and significant effect towards hemodialysis patient satisfaction at Rumah Sakit Haji Jakarta. The outcome of this study is expected to become a reference and guide for health care provider in increasing patient satisfaction.